Pengaruh Kebijakan Perpajakan dan Inflasi Terhadap Penerimaan Pajak - Nindita Dwi Marlyanti; Aristha Purwanthari Sawitri (INVENTORY: JURNAL AKUNTANSI, 2020)
Indonesia needs to make arrangements and implementation of national development aimed at realizing welfare for the community. The national development cost is derived from the largest tax sector. The objective of the research is to analyze the influence of Self Assessment System, tax audit, tax collection and inflation on VAT acceptance in KPP Pratama Surabaya Karangpilang. The documentation method is used to obtain the VAT Acceptance report data KPP Pratama Surabaya Karangpilang period 2015-2018 and written data from Bank Indonesia with purposive sampling technique. Samples obtained 48 months during the period 2015-2018. Partial research results show if only tax billing variables have an effect on VAT acceptance in KPP Pratama Surabaya Karangpilang. Based on the results of the research obtained, KPP Pratama Surabaya is expected to increase service and outreach activities in order to provide understanding and awareness of the importance of paying taxesKeywords; Tax; PPN and Inflation